Back Cover: Enhanced Photocatalytic Water Splitting in a C2N Monolayer by C‐Site Isoelectronic Substitution (ChemPhysChem 12/2017). Issue 12 (12th June 2017) - Kishore, M.R. Ashwin; Ravindran, P.
Abstract : The Back Cover picture illustrates that Si and Ge substitution at the C‐site in C2 N monolayers suitably modifies (i.e. pushes up) the band‐edge positions with respect to water redox potentials for water splitting and thus enhances the photocatalytic efficiency. More information can be found in the Full Paper by M. R. A. Kishore and P. Ravindran onpage 1526 in Issue 12, 2017 (DOI:10.1002/cphc.201700165 ).